Implementing Azure Cloud design patterns : implement efficient design patterns for data management, high availability, monitoring, and other popular patterns on your Azure Cloud /: implement efficient design patterns for data management, high availability, monitoring, and other popular patterns on your Azure Cloud. (2018) - Michalski, Oliver; Demiliani, Stefano
No abstract available